Actualization of Pancasila Value in Law Enforcement in the Field of Taxation in Indonesia - Ariyanto, Agung Pamula (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2025)
Pancasila, as the basis of the Indonesian state, has a fundamental role in every aspect of national and state life, including the taxation system. Law enforcement in the field of taxation must reflect the values of Pancasila to create justice, legal certainty, and prosperity for society. This research analyzes how Pancasila values are actualized in Indonesia's taxation system and law enforcement. The research method used is a normative approach with a literature study of statutory regulations, court decisions, and related literature. The research results show that the principles of Pancasila, such as social justice, deliberation, and unity, have strong relevance in building a taxation system that is fairer and oriented towards people's welfare. However, there are still challenges in implementing these values, especially in transparency, tax compliance, and protecting taxpayers' rights. Therefore, it is necessary to strengthen policies and legal reforms based on Pancasila values to create a more just tax system.